Paleohydrology, Sedimentology, and Geochemistry of Two Meromictic Saline Lakes in Southern Saskatchewan - Last, William; Slezak, Laurie (Géographie physique et Quaternaire, 1986)
ABSTRACTThe Northern Great Plains of western Canada contain numerous saline and hypersaline lakes. Most of these lakes are shallow (< 3 m) and exhibit playa characteristics. Some, however, are relatively deep, permanent water bodies. The sediment records of these deep perennial saline lakes offer an excellent opportunity to evaluate key paleohydrologic and hydrochemical parameters. Variations in these parameters may, in turn, be interpreted with respect to climatic fluctuations in the region. Waldsea and Deadmoose lakes, located in south-central Saskatchewan, are both presently meromictic, with saline Mg-Na-SO4-CI waters overlying denser hypersaline brines of similar composition. The modern sediments of the lakes consist of a mixture of organic matter, finegrained detrital elastics (mainly clay minerals, carbonate minerals, quartz, and feldspars), and finely crystalline endogenic/authigenic precipitates (aragonite, gypsum, calcite, pyrite, and mirabilite). Variations in mineralogy and chemistry of sediment cores from the morphologically simple Waldsea basin show that the lake was much shallower and more saline about 4000 years ago. Although water levels have since generally increased in the basin giving rise to higher organic productivity and greater inorganic carbonate precipitation, there is also evidence of several hydrologie reversals during the last 2000 years. The stratigraphy preserved in nearby Deadmoose Lake is much more complex because of the irregular basin morphology. Lower water levels about 1000 years ago created several isolated but still relatively deep lakes in the Deadmoose basin.